Genetically Engineering Coral for Conservation: Psychological Correlates of Public Acceptability - Aditi Mankad (Frontiers Media S.A., 2021)
Coral bleaching contributes to widespread reef loss globally, including Australia’s World Heritage site, the Great Barrier Reef. Synthetic biology offers the potential to isolate and cultivate strains of coral that can naturally withstand higher sea surface temperatures associated with climate change. A national survey was conducted (N = 1,148 Australians) measuring psychological predictors of support for a synthetic biology conservation solution to coral loss. The analysis showed a partially mediated path model was useful in explaining a significant amount of variance in public support for the development of genetically engineered coral for conservation (R2 = 0.40) and in willingness to visit parts of the Great Barrier Reef where genetically engineered coral had (hypothetically) been introduced (R2 = 0.24). Participants were moderately strongly supportive of technology development and were most keen to implement genetically engineered coral with between 50 and 70% of reef remaining intact; recent estimates of coral cover across the Great Barrier Reef are well below that already. There was a negative association between perceived risks of genetically engineered coral and public support; however, perceived benefit of genetically engineered coral in protecting the reef and relative advantage of a synthetic biology solution over existing protection strategies were the most influential predictors of public support. The findings suggest that the general public are not averse to the development of a synthetic biology solution for restoring the reef, and they may be especially influenced by whether the synthetic biology solution is shown to be efficacious, particularly in comparison to other conservation solutions. However, support for a synthetic biology intervention is conditional and many participants expressed concerns about possible long-term impacts on humans, animals, and the environment as a result of deploying engineered coral.